+0  
 
0
97
1
avatar

If \(\displaystyle{f(x)=x^{(x+1)}(x+2)^{(x+3)}}\), then find the value of \(f(0)+f(-1)+f(-2)+f(-3)\).

 Oct 30, 2019
 #1
avatar+107011 
+1

f(0)  =  0^(0 + 1)*(0 +2)^(0 + 3)  =  0^1 * 2^3    = 0

f(-1)  = (-1)^(-1+1)*(-1+ 2)^(-1+3)  = (-1)^0 * (1)^2  = 1

f(-2)  = (-2)^(-2 + 1) * ( -2 + 2)^(-2 + 3)  =  (-2)^(-1) * (0)^(1)  =  0

f(-3)  = (-3)^(-3 + 1) * ( -3 + 2)^(0)  = (-3)^(-2) * (-1)^0  =  1/(-3)^2  = 1/9

 

So

 

0 + 1 + 0 +1/9   =

 

1 + 1/9  =

 

10 / 9

 

 

cool cool cool

 Oct 30, 2019

14 Online Users